Advanced ceramic coatings for emerging applications - Gupta, Ram K. (Elsevier Series on Advanced Ceramic Materials Series., 2023)
Advanced Ceramic Coatings for Emerging Applications covers new developments in automotive, construction, electronic, space and defense industries. The book is one of four volumes that together provide a comprehensive resource in the field of Advanced Ceramic Coatings, also including titles covering fundamentals, manufacturing and classification, energy and biomedical applications. These books will be extremely useful for academic and industrial researchers and practicing engineers who need to find reliable and up-to-date information about recent progresses and new developments in the field of advanced ceramic coatings. These books will also be of value to early career scientists providing background knowledge to the field. Smart ceramic coatings containing multifunctional components are now finding application in transportation and automotive industries, in electronics, and energy, sectors, in aerospace and defense, and in industrial goods and healthcare. Their wide application and stability in harsh environments are only possible due to the stability of the inorganic components that are used in ceramic coatings.